Propagação vegetativa de Anacardium othonianum - Silva Junior, Francisco José Gomes da (2017)
Cashew fruit has great economic and social importance for the Brazilian Northeast, especially for the states of Ceará, Rio Grande do Norte and Piauí, as it is responsible for generating about 250 thousand direct and indirect jobs during the year. Thus, it is of great relevance to maintain the genetic variability of the genus in order to use it in breeding programs. The Caju Active Germplasm Bank (BAG), with the purpose of enriching, characterizing, documenting and making available conserved accesses and as a task of documentation and conservation of germplasm, a morphological, agronomic and molecular characterization. For this purpose, the cashew germplasm bank was created with the purpose of enriching, characterizing, documenting and facilitating the use of the conserved accessions. The cashew germplasm bank has 656 accessions, most of which are Anacardium occidentale, but also represent other cashew species, such as the Anacardium othonianum. Among the management challenges of the cashew germplasm bank are the overcoming of variance in relation to the number of plants per accession, due to the entrance of the materials by seeds; the renewal and organization of the orchard, which is very old, unproductive and cultivated in discontinued areas so the collection is being cloned and replanted in an uninterrupted area. The methodology used for vegetative propagation of A. occidentale is a lateral grafting however, there is no recommended methodology for A. othonianum. So the objective of this work was to evaluate two forms of vegetative propagation for the Anacardium othonianum: grafting and cutting and observing anatomical aspects of the cuttings, aiming at the cloning of accessions in the cashew germplasm bank. The experiments were conducted at the experimental station of Embrapa Agroindústria Tropical, in Pacajus, Ceará. For grafting, three accessions were used as rootstocks, two accessions of A. othonianum (B 194 and B 626) and one cultivar of A. occidentale (CCP 06); and three accessions of A. othonianum (B 144, B 626 and B 634) as grafts. For the cutting, two different accessions of A. othonianum (B 625 and B 634) and one cultivar of A. occidentale (CCP 76) were used, the cuttings were submitted to a rooting stimulator, prepared with and without leaves (two to three apical half-cut leaves) and planted on different substrates (commercial substrate and sand), in addition, the cuttings were observed during 5 days for the epidermis and the loss of humidity. In relation to grafting the percentage of viability was very low and about the cuttings the mortality was generalized, which did not allow to performed the statistical analysis of the data. Grafts and cuttings darkened and dried before there was any budding. Only the A. othonianum graft (B 626) obtained a small rate of viability on the different rootstocks. It was evidenced the presence of phenolic compounds in the parenchyma regions of the marrow, xylem and phloem of the stems sections. As the days passed, an increase of the possible phenolic compounds and their intensification on the third day of observation were observed. Disintegration of tissues was also observed, especially in B 634 accession. For CCP 76 and B 625 there was some evidence of proliferating meristematic tissue without, however, an evolution to rooting, probably due to the abundance of oxidized materials or phenolic compounds. Within the experimental conditions in which the experiments were carried out it was noticed that the lateral grafting graft commonly used for A. occidentale, is not feasible for cloning of A. othonianum, as well as the cutting and that the compatibility between the scion and rootstock is genotype dependent. It is also concluded that A. othonianum and A. occidentale species are difficult to rooting and have a high degree of oxidation. Other attempts at grafting and cutting with other forms of plant incubation and the use of antioxidant solutions, as well as the search for rootstocks with broad aptitude are suggested.